Prescribed and self-reported seasonal training of distance runners - Hewson, D. J.; Hopkins, W. G. (Journal of Sports Sciences, 1995)
A survey of 123 distance-running coaches and their best runners was undertaken to describe prescribed seasonal training and its relationship to the performance and self-reported training of the runners. The runners were 43 females and 80 males, aged 24 +/- 8 years (mean +/- S.D.), training for events from 800 m to the marathon, with seasonal best paces of 86 +/- 6% of sex- and age-group world records. The coaches and runners completed a questionnaire on typical weekly volumes of interval and strength training, and typical weekly volumes and paces of moderate and hard continuous running, for build-up, pre-competition, competition and post-competition phases of a season. Prescribed training decreased in volume and increased in intensity from the build-up through to the competition phase, and had similarities with 'long slow distance' training. Coaches of the faster runners prescribed longer build-ups, greater volumes of moderate continuous running and slower relative paces of continuous running (r = 0.19-0.36, P < 0.05), suggesting beneficial effects of not training close to competition pace. The mean training volumes and paces prescribed by the coaches were similar to those reported by the runners, but the correlations between prescribed and reported training were poor (r = 0.2-0.6). Coaches may therefore need to monitor their runners' training more closely.